Etudes for Solo trumpet of T. Dokschitzer: aspects of artistic and instructive stylistics (International Journal of Scientific Research and Management (IJSRM), 2021)
The article is devoted to the consideration of aspects of artistic and instructive stylistics in etudes for the Solo trumpet by T. Dokschitzer’s “Romantic Pictures”. Features of the author’s attitude to the genre of etude are highlighted. For the first time, the characteristic of all 20 etudes of the collection was proposed, in which the cycle features can be seen. This is reflected in the presence of several genre groups of etudes, combined on the basis of the types of “programity” and the relevant articulation means. A characteristic feature of all the etudes of the collection is the subordination of technical tasks to artistic purposes, which allows to determine the proposed by T. Dokschitzer type of etude for the trumpet as a musical miniature. As for performance, the etudes of the collection are designed for sufficiently trained trumpeters, but allow the choice of plays by the degree of their difficulty. There are also combinations of several etudes, which presupposes not only educational, but also concert use. Keywords: etude genre, etude for trumpet, T. Dokschitzer, “Romantic Pictures” by T. Dokschitzer, etudes by T. Dokschitzer as artistic and instructive plays-miniatures.